The role of leadership, communication and work environment in influencing employee performance - Dharmawati Djaharuddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
The purpose of this study is to analyze and examine the partial and concurrent influence of leadership, communication, and work environment variables on employee performance. This research was conducted at the Banggai Laut Regency's Department of Education, Culture, Youth, and Sports in Central Sulawesi Province. The research data were gathered through the distribution of questionnaires and the participation of 36 employees. The regression method was used to analyze the data via the SPSS tool. The study's findings indicate that there is a significant relationship between leadership, communication, and work environment and employee performance, which means that if each of these three variables is implemented at the Banggai Laut Regency's Department of Education, Culture, Youth, and Sports following applicable regulations, employee performance will be significantly impacted. The work environment variable is the most significant factor affecting employee performances.